PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING DALAM PEMBELAJARAN TERHADAP PEMBENTUKAN KARAKTER SISWA DI ERA PEMBELAJARAN ONLINE - Tambunan, Janwar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2022)
The purpose of this study was to see the effect of the Quantum Teaching learning model used by Christian Religious Education teachers in the formation of student character. The sample in this study was 50 people. This study used descriptive methods, while the data analysis carried out in the hypothesis research was Pearson's product moment correlation with data collection tools, namely a questionnaire for Variable X (Influence of Quantum Teaching Learning Model) and Variable Y (Student Character Building) The statistical test used in this research is using the Pearson Product Moment Correlation statistical test. From the test results obtained correlation test (r) 0.96 with a determination test of 92% and to determine whether or not the correlation coefficient is significant at the real level (α) = 0.05, the